MY VISION, MISSION AND DEVELOPMENT GOALS FOR THE POLYTECHNIC UNIVERSITY OF THEPHILIPPINES - De Guzman, Emanuel (Social Sciences and Development Review, 2012)
The concept of epistemic community as applied in the academe has been the selling point in the crafting of the vision, mission and development goals of the author in his initial vie for the presidency of PUP. Using this context “clearing the path towards making PUP a reputable academic and professional epistemic community,” he proposes that changes could be done , in terms of devolution and democratization of processes, transparency in rewards and sanctions, refurbishing classrooms and creation of spaces for students to decongest the main campus, reconceptualization and reinstitutionalization of the student council and the student paper, and lobby for higher state subsidy as well as look for opportunities to augment budget through research and academic excellence.